Model Proses Pembelajaran Akuntansi: Peran Teknologi Informasi Dikalangan Dosen Akuntansi Pada Masa Pandemi - Hanif, Aisha; Yani, Muhammad; Ravita Hanun, Nur (Akuntansi : Jurnal Akuntansi Integratif, 2021)
Abstract This study aims to test empirically: 1) The role of IT 2) The effect of the accounting learning process 3) Institutional response to Covid-19 on Teaching Performance of Accounting lecturers with Transfer Knowledge as an Intervening Variable, which consists of three independent variables, namely the Role of IT (X1) , Accounting Learning Process (X2), Institutional Response to Covid-19 (X3) with the dependent variable Accounting Lecturer Teaching Performance (Y), and the intervening variable Transfer Knowledge (Z). The source of the data used in this study comes from the answers to the questionnaires distributed to the Accounting Lecturers in Indonesia. The questionnaire was distributed via the geogle link from, the respondents who filled in were 124 people. The analysis technique uses data that includes the outer model, inner model and path analysis with Smart PLS 3.0. The results of this study are that the accounting learning process and institutional responses to Covid-19 have a positive and significant effect on the teaching performance of accounting lecturers and are mediated by transfer knowledge.